Strategi Digital Marketing Untuk Meningkatkan Pemasaran UMKM Di Kelurahan Turi Kota Blitar - Dhea Restina, Amanda; Aji putra, Chrystia; Dwi Evitasari, Rista; Windi Prawita, Desy; Nailinajiyah Darmayanti, Faza; Shafia Putri Alyzia, Nadia; Nurqodri, Alifiyasintadewi; Puji Utomo, Dimas; Luhur Pambudi, Prima (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
The development of technology today has greatly improved, resulting in influential business efforts of both large and small. Activities in promoting products globally can increase sales volume and profit by using digital marketing. In the majesty of Turi, there are quite a few societies that do business. However, among the MSMEs that have developed, they are still hampered by a lack of knowledge about online marketing. The reason many business actors do not carry out E-commerce activities is because they are more comfortable selling offline (directly), not interested in selling online and lack of knowledge or skills in online marketing. Therefore, a digital marketing strategy activity was held to increase the marketing of MSMEs in Turi Village in Blitar City. The goal is a strategic effort to increase marketing potential through digital marketing for MSMEs in Turi Village, Sukorejo District, Blitar City. The methods used in this activity are socialization, discussion, training and mentoring. The digital marketing strategy to increase marketing for MSMEs in Turi Village, Sukorejo District, Blitar City is carried out in several stages, namely digital marketing socialization and digital marketing training and assistance. It is hoped that MSMEs can apply product photos to attract consumer interest, use a marketplace, create a website to promote MSME products in Turi Village to increase marketing through social media